IMPACT ANALYSIS OF IMPLEMENTATION OF INHERITANCE LAW IN AL FATAH - Rahman Arief, Kholid Abdul; Armayanti, Retha; Amalia, Nurul (Jurnal Ushuluddin, 2025)
The implementation of Islamic inheritance law at Al-Fatah Pesantren has shown positive impacts in creating peace and justice in accordance with the principles of Islamic Sharia, based on the Qur'an and Hadith. However, issues arise as some members of the community do not fully agree due to differences in understanding, traditions, or personal interests. This study aims to identify the positive impacts of implementing Islamic inheritance law and analyze the community's response to its application within the pesantren. Using qualitative methods such as interviews, observations, and documentation studies, the research results show that this implementation is effective in reducing family conflicts. Nevertheless, further socialization and education are needed to overcome resistance and strengthen understanding of the justice of Islamic inheritance law to achieve broader acceptance within the pesantren community